SOLUTIONS TO MATHEMATICS 17 EXERCISES Systems of Linear Equations (Two and Three Variables) 2016 September 24
I. We intend to solve the following systems of equations. As we stated in a previous post, we provide minimal details about the solutions (especially when the system looks a little weird), and go straight to the answers. The idea of the solution makes use of the two techniques we discussed last time: elimination by substitution, and elimination by addition. And thus, without further ado:
(a)
(b)
(c)
(d)
(e)
(f)
(g)
(h)
(i)
^{} 2x − y = 24
x + y = −3 ^{=}^{⇒}
x = 7, y = −10
^{} 8s − 2t + 1 = 0
= ^{1}
s
= −1, t = − ^{7}
2
_{2} s − 3 ^{=}^{⇒}
t
2x + 3y − 12 = 0
4x + 6y −
no solution
6 = 0 ^{=}^{⇒}
^{} 3k + 4m − 4 = 0
5k + 2m − 8 = 0 ^{=}^{⇒}
k
= ^{1}^{2} , m = − ^{2}
7
7
3u −
v = 4
−6u + 2v = 8 ^{=}^{⇒}
4
x
2
x
^{+} _{y} 3
5
^{−} _{y}
= 27
= −19
=⇒
Here, we can use the substitution u = 
1 

_{x} , v 
= 
system
1
_{y} , and end up with the equivalent
^{} 4u + 3v = 27
2u − 5v = −19
which we can solve as we had done before.
4x + 3y
+
x −
−4x + 2y
2x − 2y
2x
c
+
− 2l +
−2c + 3l
z = 1
y − 2z = −6
z = −2
=⇒
x = −1, y = 1, z = 2
= 3
= −5
− 3y + 4z = −2
+ 3z
− 7z
+ 4r
r
=⇒
x = 1, y = 2, z = 1
c = 3, l = 4, r = 1
= 8
= −5
= 1
=⇒
2x + 3y − z
7
= 0
= 9
(j)
1 

=⇒ 
x = 
_{2} , y = 3, z = 10 
a = 3, b = 5, c = 2
−3x +
a + b
2a
−
3
u ^{−}
−
2
u
2
y
−
2
_{v}
1
v ^{+}
^{+}
2y + ^{z} _{2} = 11
= 8
(k)
c = 4
b + 2c = 9
=⇒
= 1
= 5
= 5
1
_{w}
1
_{w}
=⇒ 
u = −1, v = − _{2} , w = ^{1} 3 1 

1 _{v} , and c = 
1 
(l)
If we let a = ^{1}
_{u} , b =
_{w} , then we have this system:
3a − 2b 
= 1 

− 
b + 2c 
= 5 
−2a
+
c = 5
Which gives us a = −1, b = −2, c = −3. By substituting back to u, v, w, we get the answer above.
(m)
^{} 4x
^{2}
+ y ^{2}
x ^{2} +
= 17 y = 5
^{=}^{⇒}
x = 2,
y = 1 or x = −2,
y = 1 or x = ^{√} 2,
y = 3 or x = − ^{√} 2,
y = 3
Weird stuﬀ going on  there’s x ^{2} ! We can do two things:
i. From the second equation, we have y = 5 − x ^{2} . We can substitute this into the ﬁrst equation, to get x ^{4} − 6x ^{2} + 8 = 0, a solvable equation in quadratic form. The
solutions here are x _{1} = 4, x _{2} = −4, x _{3} = ^{√} 2, and x _{4} = − ^{√} 2. The ﬁrst two solutions for x give y _{1} = −4, and the second two give us y _{2} = 3. ii. OR, we can eliminate x ^{2} by multiplying the second equation by 4 and adding it to the ﬁrst equation, to get y ^{2} − 4y = −3 =⇒ y ^{2} − 4y + 3 = 0. Thus, we have y _{1} = 1,
and y _{2} = 3, which give us, in turn, x _{1}_{a} = 2, x _{1}_{b} = −2, and x _{2}_{a} = ^{√} 2, x _{2}_{b} = − ^{√} 2.
Quite tedious a checking part, it is. But we are checking eight pairs of solutions, four of which qualify as our ﬁnal answers. (When we get to Math 54, we can recall this exercise and see what exactly we are doing: we are ﬁnding the coordinates of the points of intersection of an ellipse and a parabola, which can intersect in at most four points.)
(n)
x ^{2} + y ^{2} = 1
−2x + 3y = 6 ^{=}^{⇒}
no solution
We can do some substitution here, either for x in terms of y , or for y in terms of x. The resulting equation turns out to have fractions all over, but is still easy to solve. Or is it?
As usual, we can do another solution: we multiply the ﬁrst equation by 9, to get
9x ^{2} +9y ^{2} = 9 = (3x) ^{2} +(3y) ^{2} . Now, from the second equation, we can write 3y = 2x +6, and replace the 3y in our ﬁrst equation: (3x) ^{2} + (2x + 6) ^{2} = 9 =⇒ 13x ^{2} + 24x + 27 = 0. We can check that D = 24 ^{2} − 4(13)(27) < 0. Hence, no solution for x exists, and so we say as above.
(o)
^{} 4x ^{2} − y ^{2}
= 4 y = x ^{2}
^{=}^{⇒}
x = ^{√} 2,
y = 2 or x = − ^{√} 2,
y = 2
Here, we have no choice but to substitute y = x ^{2} into the ﬁrst equation, and solve for x as we had done before.
(p)
(q)
2(x ^{2} + 2x) −
3(x ^{2} + 2x) − 2y = −7 ^{=}^{⇒}
y = 4
= −7
x = −5, y = 26 or x = 3, 
y = 26 

x = 0, 
y = 0 or x = 0, 
y = 8 
^{=}^{⇒}
^{} x ^{2} + y ^{2} − 8y
x ^{2} + y ^{2} = −6x + 8y
Seems like there’s not much to be stressed about here: we can simply do some sub stitution to get −6x + 8y − 8y = −7. Then we can solve for x and y.
(r)
⇐⇒
x ^{2} + (y − 4) ^{2} = 9. So we actually have a circle ! Similarly, the second equation becomes (x + 3) ^{2} + (y − 4) ^{2} = 25, another circle. So we can subtract these equations to get (x + 3) ^{2} − x ^{2} = 9, which is a relatively nicer equation to stare at.
But we have to look closely: x ^{2} + y ^{2} − 8y
= −7 ⇐⇒ x ^{2} + y ^{2} − 8y + 16 = 9
4x ^{2} −
−2x ^{2} −
y ^{2}
y ^{2} − 3z
+
z ^{2}
= 1
^{2} = −9
3x ^{2} + 4y ^{2} − 2z ^{2} = 17
=⇒
x = ±1, y = ±2, z = ±1
Here, we committed another braindraining error: the second equation should have 9 on the right side, not 6. (That statement applies if ever you took a crack at this system. Otherwise, we can proceed.)
We can let a = x ^{2} , b = y ^{2} , c = z ^{2} , and get the equivalent system
b +
4a −
c = 1
= −9
b − 3c
−2a −
3a + 4b − 2c = 17
And by getting the values for a, b, and c and going back to x, y, and z, we get the eight answers above. (We condensed the answers to save space; basically, we mix and match the positive values and negative values to get the answers.)
II.
We try to ﬁnd the points of intersection of the following curves, which we put in the rightmost column. Here is where we express our answers as solution sets, since we can think of this part as getting the intersection of sets of points satisfying the equations we have.
Curve 1 
Curve 2 
Points of Intersection 

i. 4x + 3y + 10 = 0 
−3x + 5y + 7 = 0 
{(1, −2)} 

ii. y = x − 1 
y 
= −2x ^{2} + 6x + 2 y = x ^{2} + 2x + 6 
{ ^{} − ^{1} _{2} , − ^{3} ^{} , (3, 2)} 2 

iii. 8x − 1 y = 
∅ 

^{2} iv. y x + 
^{2} 
= 10 
3y = 
x + 10 
{(−1, 3)} {(3, 1), (−3, −1)} 

v. x ^{2} + y 
^{2} 
= 10 
3y = x 3y = x + 15 

vi. x ^{2} + 
y ^{2} = 10 
∅ 

vii. y = 
x ^{2} + 8x 
y 
= −2x ^{2} − x + 12 
{(−4, −16), (1, 9)} 

viii. y = x ^{2} + 6x 
y = −x ^{2} − 2x − 8 x ^{2} + y ^{2} + 8y − 10 = 0 
{(−2, −8)} {(1, 1), (−5, −3)} {(1, 1)} 

ix. (x + 4) ^{2} + (y − 2) ^{2} = 26 

x. x ^{2} + y ^{2} = 2 
(x + 1) ^{2} + (y + 1) ^{2} = 8 
The ﬁrst row concerns two linear equations, which is easy enough. The next two rows have
a line and a parabola, and can be solved equally easily. The next three rows have a line and
a circle, which can intersect at two points, one point (in which case the line is to the circle), or no point at all.
The last four rows concern the “unnecessary” stuﬀ pointed out by your lecture instruc
tor last time. When two parabolas intersect, we expect at most four points of intersection,
if they do intersect. (However, we only consider cases with only zero, one, or two points of
intersection. For now.) Rows 7 and 8 can be easily solved still, since we can substitute y in either of the equations by the other expression for y.
Rows 9 and 10 concern two circles, which can intersect in zero, one, or two points as well. We just look at what happens in each row:
(ix) (x + 4) ^{2} + (y − 2) ^{2} = 26,
x ^{2} + y ^{2} + 8y − 10 = 0
The ﬁrst equation can be rewritten as x ^{2} +y ^{2} + 8x − 4y − 6 = 0, or (x ^{2} +y ^{2} + 8y − 10) + 8x − 12y + 4 = 0. Hence, we can actually write 0 = 8x − 12y + 4 (why?), or 0 = 2x − 3y + 1. We can thus isolate either x or y from this equation, and substitute it into the equation of the second circle (for easier computation). So we should an equation, with solutions y = 1, y = 3 (if we chose the xsubstitution) or x = 1, x = −5 (if we chose the ysubstitution). A little more checking, and we get the solutions above.
(x)
x ^{2} + y ^{2} = 2,
(x + 1) ^{2} + (y + 1) ^{2} = 8
Here, we expand the second equation: x ^{2} + y ^{2} + 2x + 2y − 6 = 0. Since x ^{2} + y ^{2} = 2, we can use substitution to get 2x + 2y − 4 = 0 ⇐⇒ y = 2 − x. We can now use this to solve the ﬁrst equation in terms of x, and we should end up with 2x ^{2} − 4x + 2 = 0, giving us x = 1 and two possible values for y. But only one will satisfy the equations we have, and that’s the content of our SS.
III.
The sum of the digits of a threedigit number is 18. Interchanging the second and third digit will increase the number by 36. If the ﬁrst and the third digits were interchanged, the new number is 99 less than the original number. Find the original number.
If we represent our threedigit number using the digits a, b, c, then we have the original number as 100a + 10b + c, and the following equations:
a 
+ 
b + 
c = 18 

100a + 
b + 
10c 
= 100a + 10b + c + 36 
a + 10b + 100c = 100a + 10b + c − 99
which is equivalent to this:
Thus we get a = 8, b = 3, c = 7, and
IV. Find the elements of the set
a + b + c
= 18
− b + c = 4
a − c = 1
our original number is 837
.
R = {(x, y) ∈ ^{2}  10x ^{2} − xy + 4y ^{2} = 28 and 2x ^{2} − 3xy − 2y ^{2} = 0}
As we pointed out last time, it helps if we remove the xy term:
10x ^{2} − xy + 4y ^{2} = 28
2x ^{2} − 3xy − 2y ^{2} = 0
=⇒ ^{} −30x ^{2} + 3xy − 12y ^{2} = −84
2x ^{2} − 3xy −
2y ^{2} = 0
Adding up the two equations on the right gives us 2x ^{2} + y ^{2} = 6. And we should see that we can’t do anything other than saying
R = {(x, y) ∈ ^{2}  2x ^{2} + y ^{2} = 6}
V. Find the equation of the parabola and circle containing the following points, if they exist.
(a) 
A _{1} (1, 11), A _{2} (0, 6), A _{3} (2, 18) 
(b) 
B _{1} (5, −2), B _{2} (−1, −4), B _{3} (3, 0) 
Here, we can use the following equations:
(i) For ﬁnding the equation of the parabola, we use the general quadratic equation y = ax ^{2} + bx + c, and generate three equations from the three points we have.
(ii) For the equation of the circle, we can use the general form of the equation for a circle, x ^{2} + y ^{2} + dx + ey + f = 0, and obtain three equations in d, e, and f .
We use these equations for item (b), and leave (a) for you to solve.
For the parabola, we get
c
− 4 = a(−1) ^{2} + b(−1) + c
c
− 2 = a(5) ^{2}
+ 0 = a(3) ^{2}
+
+
b(5)
b(3)
+
+
=⇒
25a + 5b + c = −2
b + c = −4
a −
9a + 3b + c = 0
1
And we should get a = − _{3} , b = − ^{5} _{3} , c = −2. Hence, our parabola containing B _{1} , B _{2} and B _{3}
has equation
y
= − _{3} x ^{2} + ^{5}
1
_{3} x − 2
.
For the circle, we get the following system:
5d − 2e + f
−d − 4e + f
= −29
= −17
3d
+ f = −9
And we should end up with d = −4, e = 6, f = 3, and the equation
(This can always be converted into the other form.) You can solve (a) if you want, and check
nice. But chances are low that any problem of the type from parts IVV
would ever show up in the future. We should be prepared, however, when similar problems arise elsewhere.
if the answer is
x ^{2} + y ^{2} − 4x + 6y + 3 = 0
.
/michaelbay20160924
Mult mai mult decât documente.
Descoperiți tot ce are Scribd de oferit, inclusiv cărți și cărți audio de la editori majori.
Anulați oricând.